Experiment of a novel four-spherical intrauterine contraceptive device with nickel-titanium - Yu, Jian-Chun; Zhang, Mei-Hua; Yu, Ling; Zhai, Li-Ping; Song, Xia; Dong, Fang-Di; Qiu, Yi (Clinical Journal of Obstetrics and Gynecology, 2020)
The aim of this study was to develop a novel four-spherical intrauterine contraceptive device (4-SIUD) with nickel-titanium (Ni-Ti) for human, and to evaluate the contraceptive effect. The 4-SIUD composed of 4 mesh spheres and 5 support arms. The shape of 4-SIUD was like a “T”. The height (H), upper width (D) and thickness of the 4-SIUD for macaques were 0.8 cm, 0.5 cm and 0.3 cm, and for human were 4.5 cm, 4.0 cm and 0.8 cm, respectively. The 4-SIUD was inserted into 5 macaques and pregnancy was not observed at 12 months. Three women used the 4-SIUD for 12 months, uterine perforations, expulsion, pain, and pelvic inflammatory did not occur. The results suggested that the 4-SIUD is appropriate for rhesus macaques and human use, and has a good contraceptive effect.